Pengaruh Gaya Kepemimpinan, Konflik Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variabel Intervening - Mamahit, Novita angela (Universitas Sam Ratulangi, 2016)
The purpose of this research is to find out the influence of leadership style, job conflict and job stress to staff performance with organisation commitment as a intervening variable in North Sulawesi KPU. Sample of this research is 134 people. The data collection in this research is questionaire. The method of analysing data in this research in path analysis withÂ SPSS program. This research show that leadership style, job conflict and job stress has influence significantly to staff performance while organisation commitment has notsignificant to staff performanceKeywords: leadership style, job conflict, job stress, organization commitment, performance